Ethics of the Real for Political Analysis: Reflection on the (Renewed) Conflict in Palestine - Joash Tapiheru (Jurnal Ilmu Sosial dan Ilmu Politik, 2022)
This article expounds critical reflections and analysis on the discourse regarding the conflict in Palestine. The case is posited through the lens of a certain ethical position, namely the ethics of the real and the framework that it supports, namely Lacanian Psychoanalysis. Reflecting on the impasse that the discourse on the conflict in Palestine has been confronted with, this article argues that political analysis may take insight from psychoanalysis to make the course of analysis directed toward the deconstruction of the obsessive neuroticism at the core of this impasse. In doing so, the political analysis should take a retroductive course, moving back and forth between the ontological and ontical planes of the reality analysed. This enables political analysis to account more systematically the factors of inevitable lack in the structure and split on the subject and the corresponding affective dimension, which are central in the political constitution of social formation and identity. Through the analytical lens and approach from psychoanalysis, this article investigates and demonstrates how most of the discourses on the conflict in Palestine have strong propensity to avoid the conflict, which on its turn counterintuitively serve to prolong or fan further conflict, as they focus on the neatness and seamlessness of the reality constituted through their own discourses rather than grappling with the conflict.